Does early heart rate detection and continuous monitoring have an impact on neonatal resuscitation in newborns with intact cord? – An observational study - Sushil Choudhary; Arun Singh; Anurag Pandey; Neeraj Gupta; Anil Kumar; Swasthi Kabisatpathy (Journal of Family Medicine and Primary Care)
Context: Heart rate (HR) is the most vital parameter to assess hemodynamic transition at birth. ECG is considered a gold standard for HR assessment. New devices with dry electrodes are easy to apply on a wet newborn. However, the utilization of newer technology that captures fast and reliable HR, and its impact on neonate resuscitation are yet to be explored, especially in newborns with intact cords. Aims: to detect HR early by dry electrode devices and its impact on neonatal resuscitation. Settings and Design: This is an observational study conducted at a tertiary care hospital in India. Methods and Material: A portable pulse oximeter, conventional ECG with modified 3 electrodes, and dry electrodes ECG (Neo Beat) were applied to capture HR ECG and Sp02. First reliable HR and outcomes of neonates were compared. Statistical Analysis Used: Median (IQR) was calculated for quantitative data. These were conducted using an updated version of IBM SPSS Statistics 22 software. Results: Out of 329 newborns, 24 newborns had their first documented HR of less than 100 bpm, out of which 14 (58%) initiated respiration with initial steps and the rest 10 required resuscitation (42%) in the form of positive pressure ventilation. Among newborns with a first HR of more than 100 bpm, 8 newborns (2.6%) required resuscitation. The median duration to capture the first reliable HR using dry electrodes was 15 sec (IQR 12.7–20 sec), which was much faster than the time required by conventional ECG (37 sec) and pulse oximetry (80 sec). Conclusions: First reliable HR can effectively predict the need for neonatal resuscitation. Dry electrode ECG can effectively capture continuous and reliable HR. HR trends can further assist in predicting the need for neonatal resuscitation and the efficacy of neonatal resuscitation.